2017
DOI: 10.1007/s10551-017-3674-4
|View full text |Cite
|
Sign up to set email alerts
|

The Advocate’s Own Challenges to Behave in a Sustainable Way: An Institutional Analysis of Advocacy NGOs

Abstract: Non-governmental organizations (NGOs) are increasingly important drivers for businesses' self-regulation to operate in a sustainable way. We shift the perspective on NGOs from focusing on their advocacy role to focusing on their accountability for having sustainable internal operations. In a multiple case analysis, we explore the question 'What are the drivers and barriers to sustainable conduct of NGOs that are sustainability advocates?' Drawing on institutional theory, we obtain novel insights into the legit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…While these research streams have merit for the OSCM field, we rarely found the trade-off concept being further conceptualized or sources for these trade-offs to be examined within these publications, with notable exemptions (e.g. Dabhilkar et al, 2016;Rodr ıguez et al, 2016;Brennan and Tennant, 2018;Koster et al, 2019;Longoni et al, 2019). In this light, the aim of this special issue is to foster research that more actively engages with the challenges of unanticipated outcomes, tensions and trade-offs from a conceptual stance.…”
Section: Introductionmentioning
confidence: 99%
“…While these research streams have merit for the OSCM field, we rarely found the trade-off concept being further conceptualized or sources for these trade-offs to be examined within these publications, with notable exemptions (e.g. Dabhilkar et al, 2016;Rodr ıguez et al, 2016;Brennan and Tennant, 2018;Koster et al, 2019;Longoni et al, 2019). In this light, the aim of this special issue is to foster research that more actively engages with the challenges of unanticipated outcomes, tensions and trade-offs from a conceptual stance.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review and hypotheses 2.1 Institutional theory and the determinants of corporate environmental performance Institutional theory explains that organisational behaviour is motivated not only by economic reasons but also by socially determined justifications and obligations. Institutional theory postulates that organisations are influenced by the pressures that they receive from their institutional environment in three domains: the regulatory domain, which establishes formal rules; the normative domain, understood as the set of moral and cultural norms; and the cognitive domain, referring to the perception of organisational legitimacy (Koster et al, 2019;Scott, 2008). These pressures lead entities to adapt their organisational behaviour, processes, and structures (Ortas et al, 2019;Ali et al, 2019).…”
Section: Corporate Environmental Performancementioning
confidence: 99%
“…The institutional theory is used as the theoretical background. The institutional environment delimits norms that are based on the moral and cultural standards according to which an organisation is legitimised to operate (institutional regulatory, normative, and legitimacy environment) (Koster et al. , 2019; Riquel-Ligero and Sánchez-Vargas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prominent economic reform programs are often effected through fiscal policy changes. The type and level of interventions in national economies indicate that countries are increasingly treated as manageable territories for accommodating changes planned by supranational institutions (Koster et al, 2019;Roxas and Coetzer, 2012).…”
Section: The Role Of Public Institutions In Society and Institutional...mentioning
confidence: 99%